2017
DOI: 10.1007/s10834-017-9553-4
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Economic Status in Adolescence: Determinants and Associations with Mental Health in the Norwegian Youth@Hordaland Study

Abstract: His current research is on social inequality in mental health among children and adolescents, and on psychometric methods. He received his PhD from the University of Bergen in Norway. Eric Dearing is a psychologist, professor in the Lynch School of Education at Boston College in Boston, Massachusetts (US), and a senior researcher at the Norwegian Center for Child Behavioral Development, Oslo, Norway. His research is focused on the roles of family, school, and community in the lives of children growing up poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 49 publications
(63 reference statements)
2
30
0
Order By: Relevance
“…In a review of the literature on subjective SES and health, Quon and McGrath (2014) demonstrated that lower subjective SES influences most health outcomes negatively, with particularly strong effects for mental health outcomes. This finding is in line with other studies of adolescents where subjective ratings of SES predict health outcomes at a similar level to objective SES-indicators (Bøe et al, 2018; Elgar et al, 2016; Quon & McGrath, 2014). This association between subjective SES and mental health may reflect the adverse effect of perceiving yourself to be in a lower socioeconomic position.…”
supporting
confidence: 92%
“…In a review of the literature on subjective SES and health, Quon and McGrath (2014) demonstrated that lower subjective SES influences most health outcomes negatively, with particularly strong effects for mental health outcomes. This finding is in line with other studies of adolescents where subjective ratings of SES predict health outcomes at a similar level to objective SES-indicators (Bøe et al, 2018; Elgar et al, 2016; Quon & McGrath, 2014). This association between subjective SES and mental health may reflect the adverse effect of perceiving yourself to be in a lower socioeconomic position.…”
supporting
confidence: 92%
“…This study provides a new story in the unique economic and cultural context of China, the world's largest developing country, for children's mental health-related research. This study focuses on the special group of rural households, especially poor rural households, and provides explanations from new perspectives such as perception bias and household expenditure structure, enriching the conclusions of existing research and complementing the latest literature on the causes and influence mechanisms of children's mental health [34,35,58]. In addition, the policy implications derived from this study is of great significance to improve the mental health of children from poor rural households in developing countries and regions, and helps to promote the sustainability of families and child welfare.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The family income affects children's likelihood of completing secondary education (Bratsberg 2010), and poor children have an increased risk of experiencing poverty themselves as adults (Lorentzen & Nielsen 2009). An overrepresentation of emotional problems among children from families of lower socioeconomic status as well as from low income families has also been shown (Bøe et al 2012;Bøe et al 2016;Bøe, et al 2017a;Bøe et al 2017b). The correlation between family income and children's living conditions speaks directly to the Convention on the Rights of Children (CRC).…”
Section: Introductionmentioning
confidence: 89%